Para aplacar uma grande saudade: estudo da obra memorialística de Maria Helena Cardoso (1903-1997) - Maria Ines de Moraes Marreco (2014)
This thesis, by analyzing the memorialistic work of Maria Helena Cardoso, seeks to explain the reflection of the ramifications that its route can generate: the role of memory in autobiographical texts, oblivion, fiction, the construction of the autobiographical I, identity and difference. It investigates the many faces of objectivity/subjectivity, in a game of perceptions played in the field of language, clarifying its importance as the responsible for the images which are offered to the thoughts they recall. It conceptualizes the triad author-narrator-character, demonstrating the necessity of identity between them and considering the possibility of uniting the autobiographical and fictional, through games, combinations, contracts or agreements. It analyzes the transformation occurred in the memory on Cardosos books, which starts in the traditional format of autobiography, goes thru a more elaborated diary, and ends in the form of a false romance. It demonstrates the contribution of Maria Helena Cardoso to Brazilian literature, which makes each one of her texts, a strong presence in the world of its readers.